The effect of nickel on shaping the structure of Al-Cu-Mn alloys - Górny, Marcin; Sikora, Gabriela Agnieszka; Tyrała, Edward; Repeć, Paweł (Journal of Casting & Materials Engineering, 2017)
This study investigated the effect of nickel on shaping the structure of aluminum alloys of the Al-Cu-Mn type in the “as-cast” condition and after heat treatment according to the T6 procedure. The aluminum alloys of type Al-5%Cu-1%Mn, containing nickel in a range of up to 1.9%, were taken into consideration in this work. Experiments were carried out for thin-walled thickness casting (g = 5 mm) and for reference casting with a wall thickness of g = 35 mm. Metallographic investigations of both the macro- and micro-structure were conducted to estimate the secondary dendrite arm spacing (SDAS), average diameter (dav) of the primary α (Al) grains, and surface fraction of the interdendritic phases (f). Moreover, the degree of dissolution of these interdendritic phases during the solution treatment process was determined. An SEM-EDS analysis was conducted, from which it follows that the addition of nickel at the level of 0.5% changes the un-dissolved particles from a needle-like β-Fe shape to blocky and coagulated. Higher additions of nickel starting from 0.88%) give rise to as many as four phases with higher copper content, the deficit of which results in the smaller strengthening effect of α (Al) dendrites.